2016
DOI: 10.1177/1049732315613311
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Violence in the Context of Transphobia and Criminalization

Abstract: A growing body of international evidence suggests that sex workers face a disproportionate burden of violence, with significant variations across social, cultural, and economic contexts. Research on trans sex workers has documented high incidents of violence; however investigations into the relationships between violence and social-structural contexts are limited. Therefore, the objective of this study was to qualitatively examine how social-structural contexts shape trans sex workers' experiences of violence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
95
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 67 publications
0
95
0
1
Order By: Relevance
“…Like participants in our study, trans sex workers in Ross’ studies recounted that working conditions in the West End in the 1970s and early 1980s were safer because sex workers were included in the community and were working closely with each other; however this changed dramatically with the 1984 legal injunction (Hamilton, 2014; Ross, 2012). Gentrification promotes middle-class lifestyles as well as middle-class values that regard sex work as inappropriate, which leads to policy changes and/or community campaigns to remove sex work(ers) from the neighbourhood (Lyons et al, 2015). Additionally, as has been documented in Amsterdam’s red-light district, areas to where ‘disposable’ bodies were once displaced often shifts when land value shifts due to globalization (Edelman, 2014; Poteat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Like participants in our study, trans sex workers in Ross’ studies recounted that working conditions in the West End in the 1970s and early 1980s were safer because sex workers were included in the community and were working closely with each other; however this changed dramatically with the 1984 legal injunction (Hamilton, 2014; Ross, 2012). Gentrification promotes middle-class lifestyles as well as middle-class values that regard sex work as inappropriate, which leads to policy changes and/or community campaigns to remove sex work(ers) from the neighbourhood (Lyons et al, 2015). Additionally, as has been documented in Amsterdam’s red-light district, areas to where ‘disposable’ bodies were once displaced often shifts when land value shifts due to globalization (Edelman, 2014; Poteat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The PCEPA also targets third party self-advertising, which has the potential to detrimentally impact sex workers' health and safety, and conflates sex workers with victims of violence and trafficking. Further, the PCEPA focuses on cisgender women sex workers and makes no mention of sex workers who do not identify as cis women (i.e., LGBTQ, men) [12], failing to acknowledge gender and sexual diversity of individuals who sell sex and the unique vulnerabilities faced by gender and sexual minorities [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning transphobia, different studies showed that also transgender individuals reported frequent experiences of violence and discrimination, which they ascribed to their belonging to a sexual minority group [37][38][39][40][41]. There is some evidence to support the idea that, among sexual minorities, transgender people are the most stigmatized, as they clearly violate the rules concerning gender roles [38,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%